Marketability of Assets and the Price of Risk - Stapleton, R. C.; Subrahmanyam, M. G. (Journal of Financial and Quantitative Analysis, 1979)
One of the remarkable features of the mean-variance capital asset pricing model is its robustness with respect to changes in assumption (Jensen [1]). An example of this property is given by David Mayers [4], who shows that the structure of prices of marketable assets is unaffected by relaxing the assumption that all risky assets are marketable. The result has been used in the analysis of public sector investments by Stapleton and Subrahmanyam [6]. However, although relative prices are unaffected, the general level may be due to the effect of marketability on the market price of risk.